Homologous recombination deficiency in breast cancer: genomic characteristics, clinical implications, and predictive value in neoadjuvant therapy - Huang, Jing; Luan, Feiyang; Yan, Li; Liang, Xiao; Ma, Xinyue; An, Yiyang; Hu, Sirui; Gao, Guoqiang; Wang, Yuanyuan; Yang, Jin; Dong, Danfeng (Frontiers in Oncology, 2025)
BackgroundHomologous recombination deficiency (HRD) significantly influences breast cancer development. HRD-positive breast cancer is more sensitive to DNA-targeting cytotoxic drugs, and may benefit from incorporating platinum-based agents in neoadjuvant therapy. However, standardized HRD phenotyping in China remains unclear, and research on the clinical pathological features of HRD-positive breast cancer is limited. Furthermore, its predictive value for neoadjuvant therapy efficacy is uncertain.MethodsWe employed the AmoyDx HRD kit to assess HRD status in a cohort of 133 Chinese breast cancer patients from the First Affiliated Hospital of Xi’an Jiaotong University. Differences in genomic features, clinical characteristics, and neoadjuvant therapy outcomes between HRD-positive and HRD-negative patients were evaluated.ResultsThere were 54.1% of patients exists HRD-positivite status. TP53 mutations were the most frequent among homologous recombination repair (HRR) pathway genes, showing significant differences between HRD-negative and HRD-positive groups (P = 0.004). HRD-positive had higher T stage, lower ER/PR/AR expression, higher Ki67 index, and a higher incidence of triple-negative breast cancer (TNBC) (all P < 0.05). TNBC had a higher GSS score than Luminal A patients (P = 0.001). Tumors with higher GSS scores were more likely to have low ER (P = 0.001), PR (P = 0.002) and high Ki67 expression (P = 0.001). There was no statistically significant difference in the efficacy of neoadjuvant therapies between HRD-positive and HRD-negative groups (P = 0.158). However, HRD-positive TNBC patients had a higher pathologic complete response (pCR) rate with anthracycline-based regimens (P = 0.042). No significant difference was observed in the proportion of patients experiencing progression between HRD groups (P = 0.458).ConclusionUsing a GSS-based HRD detection method, we characterized HRD genomic features, highlighting TP53 mutations and clinical-pathological associations. HRD-positive patients, especially those with high GSS scores, had lower ER/PR and higher Ki67 expression. TNBC had a higher HRD-positive rate.The role of HRD detection in predicting the efficacy of neoadjuvant therapy for breast cancer patients needs further clinical verification. In patients with TNBC, the HRD status had no significant impact on the efficacy of platinum-containing neoadjuvant therapy. However, adding anthracyclines improved outcomes for HRD-positive TNBC. This research helps establish Chinese-specific HRD detection standards and support individualized treatment strategies.